To the problem of ingredients optimization of composite materials based on epoxy resin - Buketov, A.V.; Sharko, A.V.; Zinchenko, D.A.; Stepanchikov, D.M. (Bulletin of the Karaganda University. Mathematics Series, 2017)
An algorithm of multi - criteria optimization of ingredients content of protective coatings based on analysis of changes in the values of destructive stress, modulus of elasticity in flexure, heat resistance, thermoresistance and temperature linear expansion coefficient was developed. The most optimal content of two - component disperse filler in the epoxy composite material was determined, using the method of selection by ordering objects like in example. It was found that the combination of two fillers with different dispersion improves physico - mechanical and thermal properties of materials. It was proved that for the developed matrix based on hardener PEPA (10 wt %) and epoxy oligomer ED-20 grade (100 wt %) the optimal content of two - component filler is: molybdenum disulfide - 80 wt %, microtalc - 80 wt %, silver carbonate - 0,500 wt %.